عوائق الاتصال الإلكتروني عبر النت بين الإدارة وأعضاء هيئة التدريس الجامعي - كوسة, الدكتور: بوجمعة (Sciences de l'Homme et de la Société, 2015)
تحاول هذه الدراسة التركيز فقط على مدى نضج إدارة المؤسسة الجامعية الجزائرية في تطبيق آلية الاتصال عبر الإنترنت، وبالبريد الإلكتروني على وجه الخصوص مع هيئة التدريس، ومدى تقبل هيئة التدريس لهذه الآلية؟ وهل أصلاً الطرفان مهيآن لتطبيق هذه الآلية وتقبلها والتفاعل معها إيجابيًا؟ وما هو واقع تطبيق هذه الآلية وما هي الصعوبات؟ وذلك من خلال دراسة ميدانية لعينة من هيئة التدريس لقسم علم الاجتماع في جامعة جيجل، عبر استمارة بحث ترمي لمعرفة اتجاهات هذه الفئة من هذه الآلية من التواصل، أم أن كلا الطرفين لا يزالان يؤمنان بالإدارة الورقية فقط.   Abstract : This study deals with the application of online communication mechanism, and faculty deal with e-mail in Algerian universities, to see how the faculty accepts this mechanism? Does the university administration and university professor ready to apply this mechanism and interact with it positively? What is the reality of the application of this mechanism and what are the difficulties? Researcher tries to answer these questions through a field study of a sample of the faculty of the Department of Sociology at the University of Jijel, through the search form aims to know the trends of this category of this mechanism of communication, or that both parties still believe in paper management only.